1993
DOI: 10.1111/j.1365-2494.1993.tb01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbage intake and liveweight gain of bulls and steers continuously stocked at fixed sward heights during autumn and spring

Abstract: Twu experiments were conducted to examine the relationship between sward surface height, herbage intake and liveweight gain in beef cattle grazed on pasture. In Experiment 1, two 'animal types" (18 Charolais x Angus steers and 18 Friesian bulls) were continuously grazed for 22 days during the late autumn on replicated swards maintained at sward surface heights of 6, 10 and 15 cm. Herbage intakes, assessed from the faecal concentration of chromium delivered from an intraruminal controlled release capsule and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Herbage aMI of around 10 kg/head per day measured in this experiment for 430 kg bulls is similar to the 8.7 kg OM/day reported by Morris et al (1993) for 288 kg Friesian bulls growing at 1.67 kg/day, and the 8.2 kg OM/day recorded by 439 kg Friesian steers growing at 1.51 kg/day in the trial of Zoby & Holmes (1983). It was not possible to establish whether the use of hand-plucked samples of herbage, to represent the feed apparently consumed, introduced any bias in the estimates of herbage intake for the genotypes.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Herbage aMI of around 10 kg/head per day measured in this experiment for 430 kg bulls is similar to the 8.7 kg OM/day reported by Morris et al (1993) for 288 kg Friesian bulls growing at 1.67 kg/day, and the 8.2 kg OM/day recorded by 439 kg Friesian steers growing at 1.51 kg/day in the trial of Zoby & Holmes (1983). It was not possible to establish whether the use of hand-plucked samples of herbage, to represent the feed apparently consumed, introduced any bias in the estimates of herbage intake for the genotypes.…”
Section: Discussionsupporting
confidence: 75%
“…The herbage intake data suggest that all genotypes consumed similar quantities of DM and DOMI under grazing conditions (8-10 cm SSH) which should have allowed ad libitum intakes (Morris et al 1993). Heavily muscled genotypes should therefore have reflected a greater efficiency of pasture conversion to meat gain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reflects the fact that herbage allowances were at the maximum of the LWG/ allowance asymptote relationship (Reardon 1977;Marsh 1979;Taylor & Scales 1985;Reid 1986) and were designed to allow treated animals to exhibit maximum LWG. The higher allowance in the autumn (5570 kg DM/ha) would also have allowed the animals to exhibit maximum LWG as several researchers have reported that higher pasture allowances are required in autumn than in spring for maximum growth rates of beef cattle (Reid 1986;Morris et al 1993a). Pasture quality, as measured by in vitro digestibility, was average for the type of pasture and, like herbage allowance, would have been unlikely to limit the ability of Compudose animals to express a response in voluntary intake.…”
Section: Discussionmentioning
confidence: 99%